Gniezno - Szypowski, Andrzej (1926-2010).; Szypowska, Maria (1929-2017); Wydawnictwo Sport i Turystyka (Warszawa : "Sport i Turystyka", 1961)
Wydawnictwo albumowe.
Streszcz. fr., ros., ang., niem.
Keywords: 1901-2000.; 1945-1989.; Gniezno (woj. wielkopolskie); Fotografia polska -- 1944-1989 r; Album